A Rare Cause of Reversible Splenial Lesion Syndrome (RESLES): Benign Convulsions with Mild Gastroenteritis - Nida Uysal; Afshin Dezhakam; Seda Kanmaz; Sanem Yılmaz (Journal of Pediatric Research, 2021)

(untitled)
Transient lesions involving the splenium of corpus callosum is defined as reversible splenial lesion syndrome (RESLES). Benign convulsions with mild gastroenteritis is a rare condition which may be associated with RESLES. Since the prognosis is excellent, the awareness of this association is important to prevent unnecessary investigations and anti-epileptic drug therapy.